Selling the economic miracle : economic reconstruction and politics in West Germany, 1949-1957 - Spicka, Mark E. (Monographs in German history ;, 2007)
Through an examination of election campaign propaganda and various public relations campaigns, reflecting new electioneering techniques borrowed from the United States, this work explores how conservative political and economic groups sought to construct and sell a political meaning of the Social Market Economy and the Economic Miracle in West Germany during the 1950s. The political meaning of economics contributed to conservative electoral success, constructed a new belief in the free market economy within West German society, and provided legitimacy and political stability for the new Federal Republic of Germany.